THE EFFICACY OF RECIPROCAL TEACHING METHOD IN TEACHING READING COMPREHENSION TO EFL STUDENTS - Qurrotul Ayun; Muhammad Yunus (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2017)
Abstract: The article aims to investigate the efficacy of Reciprocal Teaching Method (RTM) on reading comprehension to EFL students. The subject of the study was two classes from the second grade students of Ilmu Agama Islam (IAI) in Probolinggo. There were 44 students emerging from XI IAI 1 and XI IAI 2 which consisted of 22 each. Nonrandomized sampling was chosen to select the group. To decide the groups into control and experimental, coin was used. The XI IAI 1 class then became the experimental group (taught using reciprocal teaching method), meanwhile the XI IAI 2 was the control group (taught using conventional as it is). Both classes acquired mixed levels of reading achievement. It means that both classes were at the same level of reading comprehension. After the treatment, it revealed that those who were taught using RTM gained better result than those were taught using the conventional one.Â Key Words: Reciprocal Teaching Method, Reading Comprehension, Conventional Strategy